2019
DOI: 10.1186/s12933-019-0976-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired myocardial deformation and ventricular vascular coupling in obese adolescents with dysglycemia

Abstract: BackgroundIt is unknown that dysglycemia in obese adolescents has effects on myocardial deformation that are more pronounced when compared to obesity alone. We hypothesized that obesity associated abnormal glucose tolerance (dysglycemia) would have adverse effects on two-dimensional speckle tracking echocardiography derived longitudinal, radial and circumferential strain (LS, RS, CS) compared to age and gender lean controls. We also examined if changes in deformation would be reflected in abnormal ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Finally, impaired coronary flow reserve was reported in individuals with abnormal HOMA-IR [ 30 ], which might be involved in the association between insulin resistance and impaired LVGLS [ 31 , 32 ]. Recent studies have reported on the association between insulin resistance, dysglycemia and subclinical LV dysfunction in some clinical settings [ 33 37 ]. Ho et al showed an inverse relationship between HOMA-IR and LVGLS in the Framingham Heart Study [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, impaired coronary flow reserve was reported in individuals with abnormal HOMA-IR [ 30 ], which might be involved in the association between insulin resistance and impaired LVGLS [ 31 , 32 ]. Recent studies have reported on the association between insulin resistance, dysglycemia and subclinical LV dysfunction in some clinical settings [ 33 37 ]. Ho et al showed an inverse relationship between HOMA-IR and LVGLS in the Framingham Heart Study [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies in hypertension have found that GCPS was significantly reduced in patients with hypertrophy [17,23]. Recent studies showed the negative effects of acute hyperglycemia on systolic LV global longitudinal strain and multilayer longitudinal and circumferential strain in asymptomatic T2DM and unfavorable subclinical reductions in global and average circumferential strain in obese adolescents with dysglycemia, which may indicate the importance of intensive blood glucose control [24,25]. Moreover, epicardial adipose tissue may be associated with LV structural and functional abnormalities and exercise intolerance in T2DM patients with asymptomatic heart failure [26], and serum levels of omentin-1 and Zinc-α2-glycoprotein have been recently defined as the most important predictors for LV hypertrophy and LV diastolic dysfunction in T2DM patients [27].…”
Section: Table 4 Multivariable Association Of Diabetes With First-pasmentioning
confidence: 99%
“…It is very closely related to type 2 diabetes or metabolic syndrome, and the main pathophysiology underlying this relationship is known to be insulin resistance [37,38]. The association is considerably strong that NAFLD is present even in obese adolescents with dysglycemia [39]. NAFLD and metabolic syndrome can be considered to have similar effects on arteries, which accelerate atherogenesis via inflammation [40,41], increased oxidative stress [42], atherogenic dyslipidemia [43], imbalance of adipokines [44], and hypercoagulable status [45].…”
Section: Results In Relation To Other Studiesmentioning
confidence: 99%